CONTINUOUS MIDWIFERY CARE CONTINUITY OF CARE NY.N WITH BREAST MILK DAM AT PRATAMA TUTUN SEHATI CLINIC TANJUNG MORAWA DISTRICT DELI SERDANG REGENCY IN 2024 - tumangger, agustina; Kamelia Sinaga, S. Keb.Bd.MKM; Riska Susanti Pasaribu, SST.MKM; Nopalina Suyanti Damanik, SST, M.Psi (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
A Preliminary Survey was conducted at the Tutun Sehati Primary Clinic which is located in Tanjung Morawa District, Deli Serdang Regency and has conducted communication interpersonal with the Clinic Leader to conduct research on Tutun Clinic patients. From the results of the survey that has been carried out, data obtained from pregnant women who make 620 visits, 315 deliveries, 300 postpartum women with postpartum visits (KF 1) and there were 6 postpartum women who experienced breast milk dams, for the number of LBW there were 315 babies, and patients who made family planning visits were 150 people. And when the author conducted a survey from December 5, 2023 to February 11, 2024, the data obtained were 30 pregnant women, 10 deliveries, 9 postpartum mothers, 9 LBW babies and 2 family planning visits. Of the 30 pregnant women there was 1 pregnant woman who was willing to be carried out and given continuous care during the study, namely on behalf of NY.N age 26 years.